2018
DOI: 10.1038/s41598-018-29194-z
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the oleaginous red yeast Rhodotorula glutinis for simultaneous β-carotene and cellulase production

Abstract: Rhodotorula glutinis, an oleaginous red yeast, intrinsically produces several bio-products (i.e., lipids, carotenoids and enzymes) and is regarded as a potential host for biorefinery. In view of the limited available genetic engineering tools for this yeast, we have developed a useful genetic transformation method and transformed the β-carotene biosynthesis genes (crtI, crtE, crtYB and tHMG1) and cellulase genes (CBHI, CBHII, EgI, EgIII, EglA and BGS) into R. glutinis genome. The transformant P4-10-9-63Y-14B p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…This indicates that a higher flux is required for carotenoids than what is obtained during biomass production. Overexpression of truncated 3-hydroxy-3-methylglutaryl-CoA reductase from Kluyveromyces marxianus in combination with other genes was shown to increase βcarotene production in Rhodotorula glutinis (Pi et al, 2018). Similarly, also all enzymes of isoprene biosynthetic pathway were predicted to correlate with improved carotenoid production in R. toruloides.…”
Section: Prediction Of Potential Targets For Improved Production Of Cmentioning
confidence: 95%
See 2 more Smart Citations
“…This indicates that a higher flux is required for carotenoids than what is obtained during biomass production. Overexpression of truncated 3-hydroxy-3-methylglutaryl-CoA reductase from Kluyveromyces marxianus in combination with other genes was shown to increase βcarotene production in Rhodotorula glutinis (Pi et al, 2018). Similarly, also all enzymes of isoprene biosynthetic pathway were predicted to correlate with improved carotenoid production in R. toruloides.…”
Section: Prediction Of Potential Targets For Improved Production Of Cmentioning
confidence: 95%
“…The dimethylallyltranstransferase/geranyltranstransferase (ERG20) is involved in synthesis of farnesyl pyrophosphate (FPP) from geranyl pyrophosphate (GPP) and IPP, which is a direct metabolic precursor of carotenoids as well as ergosterol, heme A, dolichols and prenyl-adducts for prenylated proteins. A recent study has demonstrated that overexpression of the X. dendrorhous geranylgeranyl pyrophosphate (GGPP) synthase (encoded by the BTS1 gene), which is immediately downstream of ERG20, increased 330 carotenoid production in R. glutinis (Pi et al, 2018).…”
Section: Prediction Of Potential Targets For Improved Production Of Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this assumption, Liu et al [79] reported that the codon optimization was the key to Agrobacterium tumefaciensmediated transformation in R. toruloides. Pi et al [80] transformed β-carotene biosynthesis genes (crtI, crtE, crtYB and tHMG1 from X. dendrorhous and Kluyveromyces marxianus) into R. glutinis genome. The transformant P4-10-9-63Y-14b produced β-carotene (27.13 ± 0.66 mg/g) 7-fold higher than the wild type.…”
Section: Use Of Genomic Tools To Characterize Carotenoid Biosynthesismentioning
confidence: 99%
“…This indicates that a higher flux is required for carotenoids than what is obtained during biomass production. Overexpression of truncated 3‐hydroxy‐3‐methylglutaryl‐CoA reductase from Kluyveromyces marxianus in combination with other genes was shown to increase β‐carotene production in Rhodotorula glutinis (Pi et al, ). Similarly, also all enzymes of isoprene biosynthetic pathway were predicted to correlate with improved carotenoid production in R. toruloides .…”
Section: Resultsmentioning
confidence: 99%